Merging the purchasing power parity and the Phillips curve literatures: Regional evidence from Italy - Andrea Vaona (Kiel Institute for the World Economy (IfW), 2006)
The main purpose of this paper is to merge together two strands of the literature regarding, either directly or indirectly, inflation: the PPP and the Phillips curve ones. In order to accomplish this task, this contribution applies the tools of the Empirical Growth Literature and of Dynamic Panel Data estimation on a sample of 81 Italian provinces from the year 1986 to the year 1998, exploiting cross-sectional variation to avoid to use instruments not directly connected with the inflation generating process. This research strategy allows to conclude that inflation is characterized by a low degree of persistence and by conditional b-convergence across provinces. Its most suitable driving variable is the unemployment rate and there are long-term non neutralities at the regional level.
Keywords: 330; Inflation; Regionale Preisstruktur; Kaufkraftparität; Phillips-Kurve; Schätzung; Italien